The Shadow of Downturn in Law Enforcement in Indonesia - Sanusi (LEGAL BRIEF, 2021)
This writing aims to determine the extent of the downturn in law enforcement in Indonesia and the indicators of its causes, as well as whether the responsive law and Pancasila values have been implemented by law enforcement officials in law enforcement tasks. The problem of law enforcement in Indonesia leads to responsive law based on the values of Pancasila. This research is a legal research, the type of research is normative research and sociological juridical. Research using random sampling techniques with multistage sampling levels, so that variability and probability are represented to be able to find out the level of legal adversity in Indonesia and its causes indicators and how to implement responsive law and Pancasila values in law enforcement and formation in Indonesia.